RIM-Binding Protein 2 Promotes a Large Number of CaV1.3 Ca2+-Channels and Contributes to Fast Synaptic Vesicle Replenishment at Hair Cell Active Zones - Krinner, Stefanie; Butola, Tanvi; Jung, SangYong; Wichmann, Carolin; Moser, Tobias (Frontiers in Cellular Neuroscience, 2017)
Ribbon synapses of inner hair cells (IHCs) mediate high rates of synchronous exocytosis to indefatigably track the stimulating sound with sub-millisecond precision. The sophisticated molecular machinery of the inner hair cell active zone realizes this impressive performance by enabling a large number of synaptic voltage-gated CaV1.3 Ca2+-channels, their tight coupling to synaptic vesicles (SVs) and fast replenishment of fusion competent SVs. Here we studied the role of RIM-binding protein 2 (RIM-BP2)—a multidomain cytomatrix protein known to directly interact with Rab3 interacting molecules (RIMs), bassoon and CaV1.3—that is present at the inner hair cell active zones. We combined confocal and stimulated emission depletion (STED) immunofluorescence microscopy, electron tomography, patch-clamp and confocal Ca2+-imaging, as well as auditory systems physiology to explore the morphological and functional effects of genetic RIM-BP2 disruption in constitutive RIM-BP2 knockout mice. We found that RIM-BP2 (1) positively regulates the number of synaptic CaV1.3 channels and thereby facilitates synaptic vesicle release and (2) supports fast synaptic vesicle recruitment after readily releasable pool (RRP) depletion. However, Ca2+-influx—exocytosis coupling seemed unaltered for readily releasable SVs. Recordings of auditory brainstem responses (ABR) and of single auditory nerve fiber firing showed that RIM-BP2 disruption results in a mild deficit of synaptic sound encoding.